The Effect of Ideological Positions on Job Market Interaction - Anat Alexandron-Lavon; Gil S. Epstein; Renana Lindner Pomerantz (Institute of Labor Economics (IZA), 2017)
Reporters and editors may not have the same ideology. When an editor wants to employ a new reporter with a different ideology, they have to negotiate the price of moving from their own to the other's ideology. We focus on the job market for reporters, where the agents negotiate over the ideological position to be reported and wage. We adopt a spatial model in which each agent suffers a utility loss as the agreed-upon position moves away from his/her favored one. Equilibrium determines a threshold ideological gap for a match to be formed. Our analysis generates a natural separation between extreme, mildly extreme and moderate ideologies. Furthermore, we find that agents that hold extreme ideologies compromise less than moderates. This formulation may be applied to other situations in which agents involve monetary and non-monetary considerations, especially a preference for similarity.
Keywords: J32; J44; 330; ideological position; job market; media